Investigating retention patterns and recruitment dynamics of fish larvae in nearshore environments along the South-East coast of South Africa - C. Muller; K. van der Walt; F. Porri; A.-R. Childs; W.M. Potts (Estuarine, Coastal and Shelf Science, 2026)

Understanding habitat suitability for reef-forming corals in New Zealand waters and investigating the potential importance of reef-forming coral habitat for seamount-associated fishes - Beau Jarvis-Child; Arnaud Grüss; Nokuthaba Sibanda; Owen F. Anderson; Matthew H. Pinkerton; Ashley A. Rowden; Dianne M. Tracey; Malcolm R. Clark; Anthony R. Charsley (Fisheries Research, 2026)

Bushfire impacts proposed Anthropocene markers in a Southern Hemisphere World Heritage peatland - R. Carroll; G.E. Jacobsen; D.P. Child; A. Zawadzki; S. Maizma; MAC Hotchkis; J.K. Reynolds (Anthropocene, 2026)

Individual variability in the thermal limits of juvenile dusky kob Argyrosomus japonicus from a permanently open estuary - J Frachet; A-R Childs; AC Winkler; MW Farthing; CD Hempel; WM Potts (African Journal of Marine Science, 2025)

Horizon scanning to identify priority research questions for the South African marine shore-based recreational fishery - K Hewett; CS Bova; EC Butler; A-R Childs; MW Farthing; BQ Mann; JB Mann-Lang; AC Winkler; K Hyder; WM Potts (African Journal of Marine Science, 2025)

Comparing the activity of exploited and unexploited populations of a reef-dwelling seabream, Chrysoblephus laticeps , during an extreme upwelling and cold-spell event - NT Mlotshwa; MR Skeeles; MI Duncan; C Muller; WM Potts; AC Winkler; A-R Childs (African Journal of Marine Science, 2025)

Influence of the Benguela Upwelling System on the genetic connectivity of blacktail seabream Diplodus capensis across southern Africa - WF Olivier; WM Potts; A-R Childs; C Santos; PW Shaw; R Henriques (African Journal of Marine Science, 2025)

The behavioural response of an estuarine teleost (Cape stumpnose Rhabdosargus holubi ) to angler bait collection in two adjacent Eastern Cape estuaries, South Africa - EC Butler; B van Heerden; MW Farthing; A-R Childs; WM Potts (African Journal of Marine Science, 2025)

Assessment of the movement behaviour of dusky kob Argyrosomus japonicus along the coast of South Africa using 39 years of tag-recapture data from a voluntary tagging project - T Knight; M Farthing; A Winkler; BQ Mann; A-R Childs; WM Potts (African Journal of Marine Science, 2025)

Assessing the thermal tolerance of a cosmopolitan eurythermal species, the flathead mullet Mugil cephalus - DL Mukhari; A-R Childs; BA Ziko; TS Murray (African Journal of Marine Science, 2025)

Impact of catch and release on the welfare of bronze seabream Pachymetopon grande in the South African marine shore-based fishery - EC Butler; MW Farthing; CS Bova; A-R Childs; WM Potts (African Journal of Marine Science, 2025)

Impacts of Weather Anomalies and Climate on Plant Disease - Devin Kirk; Jeremy M. Cohen; Vianda Nguyen; Marissa L. Childs; Johannah E. Farner; T. Jonathan Davies; S. Luke Flory; Jason R. Rohr; Mary I. O'Connor; Erin A. Mordecai (Ecology Letters, 2025)
Predicting the effects of climate change on plant disease is critical for protecting ecosystems and food production. Here, we show how disease pressure responds to short‐term weather, historical climate and weather anomalies by compiling a global database (4339 plant–disease populations) of disease prevalence in both agricultural and wild plant systems. We hypothesised that weather and climate would play a larger role in disease in wild versus agricultural plant populations, which the results supported. In wild systems, disease prevalence peaked when the temperature was 2.7°C warmer than the historical average for the same time of year. We also found evidence of a negative interactive effect between weather anomalies and climate in wild systems, consistent with the idea that climate maladaptation can be an important driver of disease outbreaks. Temperature and precipitation had relatively little explanatory power in agricultural systems, though we observed a significant positive effect of current temperature. These results indicate that disease pressure in wild plants is sensitive to nonlinear effects of weather, weather anomalies and their interaction with historical climate. In contrast, warmer temperatures drove risks for agricultural plant disease outbreaks within the temperature range examined regardless of historical climate, suggesting vulnerability to ongoing climate change.

Comparing levoglucosan and mannosan ratios in sediments and corresponding aerosols from recent Australian fires - Harrison Stevens; Leon A. Barmuta; Zanna Chase; Krystyna M. Saunders; Atun Zawadzki; Andrew R. Bowie; Morgane M.G. Perron; Estrella Sanz Rodriguez; Brett Paull; David P. Child; Michael A.C. Hotchkis; Bernadette C. Proemse (Science of The Total Environment, 2024)

Response of demersal fishes to low dissolved oxygen events in two eutrophic estuaries - P. Nodo; A.-R. Childs; P. Pattrick; D.A. Lemley; N.C. James (Estuarine, Coastal and Shelf Science, 2023)

Movement patterns and underestimation of the maximum age of a Vulnerable endemic guitarfish species inferred from mark-recapture studies - TS Murray; C Elston; RH Bennett; A-R Childs; PD Cowley (African Journal of Marine Science, 2023)

Can social media platforms be used to foster improved environmental behaviour in recreational fisheries? - C. Allison; A.C. Winkler; A.-R. Childs; C. Muller; W.M Potts (Fisheries Research, 2023)

The nursery function of shallow nearshore and estuarine benthic habitats for demersal fishes - P. Nodo; A-R. Childs; P. Pattrick; N.C. James (Estuarine, Coastal and Shelf Science, 2023)

Whole-Ecosystem Warming Increases Plant-Available Nitrogen and Phosphorus in an Ombrotrophic Bog - Colleen M. Iversen; John Latimer; Deanne J. Brice; Joanne Childs; Holly M. Vander Stel; Camille E. Defrenne; Jake Graham; Natalie A. Griffiths; Avni Malhotra; Richard J. Norby; Keith C. Oleheiser; Jana R. Phillips; et al. (Ecosystems, 2023)

Links between behaviour and metabolic physiology in fishes in the Anthropocene - Lauren A. Bailey; Amber R. Childs; Nicola C. James; Alexander Winkler; Warren M. Potts (Reviews in Fish Biology and Fisheries, 2022)

Spawning observations of Pomadasys commersonnii in the marine section of the Knysna estuarine bay, Western Cape, South Africa - EC Butler; A-R Childs; MKS Smith; RM Foster; WM Potts (African Journal of Marine Science, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Nitrogen and phosphorus cycling in an ombrotrophic peatland: a benchmark for assessing change - Verity G. Salmon; Deanne J. Brice; Scott Bridgham; Joanne Childs; Jake Graham; Natalie A. Griffiths; Kirsten Hofmockel; Colleen M. Iversen; Terri M. Jicha; Randy K. Kolka; Joel E. Kostka; Avni Malhotra; et al. (Plant and Soil, 2021)

When cooling is worse than warming: investigations into the thermal tolerance of an endemic reef fish, Boopsoidea inornata - C Allison; C Muller; A-R Childs; W Froneman; LA Bailey; WM Potts (African Journal of Marine Science, 2021)

The influence of vector‐borne disease on human history: socio‐ecological mechanisms - Tejas S. Athni; Marta S. Shocket; Lisa I. Couper; Nicole Nova; Iain R. Caldwell; Jamie M. Caldwell; Jasmine N. Childress; Marissa L. Childs; Giulio A. De Leo; Devin G. Kirk; Andrew J. MacDonald; Kathryn Olivarius; et al. (Ecology Letters, 2021)
Vector‐borne diseases (VBDs) are embedded within complex socio‐ecological systems. While research has traditionally focused on the direct effects of VBDs on human morbidity and mortality, it is increasingly clear that their impacts are much more pervasive. VBDs are dynamically linked to feedbacks between environmental conditions, vector ecology, disease burden, and societal responses that drive transmission. As a result, VBDs have had profound influence on human history. Mechanisms include: (1) killing or debilitating large numbers of people, with demographic and population‐level impacts; (2) differentially affecting populations based on prior history of disease exposure, immunity, and resistance; (3) being weaponised to promote or justify hierarchies of power, colonialism, racism, classism and sexism; (4) catalysing changes in ideas, institutions, infrastructure, technologies and social practices in efforts to control disease outbreaks; and (5) changing human relationships with the land and environment. We use historical and archaeological evidence interpreted through an ecological lens to illustrate how VBDs have shaped society and culture, focusing on case studies from four pertinent VBDs: plague, malaria, yellow fever and trypanosomiasis. By comparing across diseases, time periods and geographies, we highlight the enormous scope and variety of mechanisms by which VBDs have influenced human history.

Susceptible host availability modulates climate effects on dengue dynamics - Nicole Nova; Ethan R. Deyle; Marta S. Shocket; Andrew J. MacDonald; Marissa L. Childs; Martin Rypdal; George Sugihara; Erin A. Mordecai (Ecology Letters, 2021)
Experiments and models suggest that climate affects mosquito‐borne disease transmission. However, disease transmission involves complex nonlinear interactions between climate and population dynamics, which makes detecting climate drivers at the population level challenging. By analysing incidence data, estimated susceptible population size, and climate data with methods based on nonlinear time series analysis (collectively referred to as empirical dynamic modelling), we identified drivers and their interactive effects on dengue dynamics in San Juan, Puerto Rico. Climatic forcing arose only when susceptible availability was high: temperature and rainfall had net positive and negative effects respectively. By capturing mechanistic, nonlinear and context‐dependent effects of population susceptibility, temperature and rainfall on dengue transmission empirically, our model improves forecast skill over recent, state‐of‐the‐art models for dengue incidence. Together, these results provide empirical evidence that the interdependence of host population susceptibility and climate drives dengue dynamics in a nonlinear and complex, yet predictable way.

Editorial overview: recommendations for the promotion of a resilient linefishery in the Anthropocene - WM Potts; CG Attwood; PD Cowley; A-R Childs; AC Winkler; MI Duncan; TS Murray; BQ Mann; JB Mann-Lang (African Journal of Marine Science, 2020)

Quantifying the impacts of abrasion and bacterial transfer when fish are exposed to sand during a catch-and-release event - RM Foster; A-R Childs; M Brooks; MW Farthing; EC Butler; WM Potts (African Journal of Marine Science, 2020)

Physiological stress response and recovery of an important estuarine fishery species, dusky kob Argyrosomus japonicus, after a simulated catch-and-release event - NK Arkert; A-R Childs; MI Duncan; M Farthing; WM Potts (African Journal of Marine Science, 2020)

Time-course of the physiological-stress response in bronze bream Pachymetopon grande following a simulated catch-and-release angling event - BA Pringle; A-R Childs; EC Butler; AC Winkler; MI Duncan; C Teta; WM Potts (African Journal of Marine Science, 2020)

A snapshot assessment of the diet of Cape fur seals Arctocephalus pusillus pusillus at Ilha dos Tigres, Angola - A Winkler; S Mannheim; A-R Childs; C Santos; C de Beer; MJ Smale; WM Potts (African Journal of Marine Science, 2019)

Can long-term content analysis of print media be used to examine species composition, population demography and changes in distributional range of recreational fishery species? - WM Potts; T Jordan; A-R Childs (African Journal of Marine Science, 2019)

A framework to measure the wildness of managed large vertebrate populations - Matthew F. Child; S. A. Jeanetta Selier; Frans G. T. Radloff; W. Andrew Taylor; Michael Hoffmann; Lizanne Nel; R. John Power; Coral Birss; Nicola C. Okes; Michael J. Peel; David Mallon; Harriet Davies‐Mostert (Conservation Biology, 2019)
As landscapes continue to fall under human influence through habitat loss and fragmentation, fencing is increasingly being used to mitigate anthropogenic threats and enhance the commercial value of wildlife. Subsequent intensification of management potentially erodes wildness by disembodying populations from landscape‐level processes, thereby disconnecting species from natural selection. Tools are needed to measure the degree to which populations of large vertebrate species in formally protected and privately owned wildlife areas are self‐sustaining and free to adapt. We devised a framework to measure such wildness based on 6 attributes relating to the evolutionary and ecological dynamics of vertebrates (space, disease and parasite resistance, exposure to predation, exposure to limitations and fluctuations of food and water supply, and reproduction). For each attribute, we set empirical, species‐specific thresholds between 5 wildness states based on quantifiable management interventions. We analysed data from 205 private wildlife properties with management objectives spanning ecotourism to consumptive utilization to test the framework on 6 herbivore species representing a range of conservation statuses and commercial values. Wildness scores among species differed significantly, and the proportion of populations identified as wild ranged from 12% to 84%, which indicates the tool detected site‐scale differences both among populations of different species and populations of the same species under different management regimes. By quantifying wildness, this framework provides practitioners with standardized measurement units that link biodiversity with the sustainable use of wildlife. Applications include informing species management plans at local scales; standardizing the inclusion of managed populations in red‐list assessments; and providing a platform for certification and regulation of wildlife‐based economies. Applying this framework may help embed wildness as a normative value in policy and mitigate the shifting baseline of what it means to truly conserve a species.

Evaluating the effects of catch-and-release angling on Cape stumpnose Rhabdosargus holubi in a South African estuary - NK Arkert; A-R Childs; MC Parkinson; AC Winkler; E Butler; S Mannheim; WM Potts (African Journal of Marine Science, 2018)

The impact of river flooding and high flow on the demersal fish assemblages of the freshwater-dominated Great Fish Estuary, South Africa - P Nodo; NC James; A-R Childs; MDV Nakin (African Journal of Marine Science, 2017)

Movement patterns of an endangered fishery species, Lithognathus lithognathus (Sparidae), and the role of no-take marine protected areas as a management tool - RH Bennett; PD Cowley; A-R Childs; CG Attwood; L Swart; TF Næsje (African Journal of Marine Science, 2017)

Reflection on the first five years of South Africa’s Acoustic Tracking Array Platform (ATAP): status, challenges and opportunities - PD Cowley; RH Bennett; A-R Childs; TS Murray (African Journal of Marine Science, 2017)

Estuarine and coastal connectivity of an estuarine-dependent fishery species, Pomadasys commersonnii (Haemulidae) - MH Dames; PD Cowley; A-R Childs; RH Bennett; EB Thorstad; TF Næsje (African Journal of Marine Science, 2017)

Philopatry and dispersal of juvenile leervis Lichia amia (Teleostei: Carangidae) tagged in a warm-temperate South African estuary - T Murray; P Cowley; A-R Childs; R Bennett (African Journal of Marine Science, 2017)

Assessing trophic adaptability is critical for understanding the response of predatory fishes to climate change: a case study of Pomatomus saltatrix in a global hotspot - WM Potts; RSJ Bealey; A-R Childs (African Journal of Marine Science, 2016)

Influence of prey abundance and abiotic factors on the long-term home-range and movement dynamics of spotted grunter Pomadasys commersonnii in an intermittently open estuary - BA Maree; PD Cowley; TF Næsje; A-R Childs; AI Terörde; EB Thorstad (African Journal of Marine Science, 2016)

The trouble with estuarine fisheries in temperate South Africa, illustrated by a case study on the Sundays Estuary - PD Cowley; A-R Childs; RH Bennett (African Journal of Marine Science, 2013)

Area-use patterns and diel movements of white steenbras Lithognathus lithognathus in a temporarily open/closed South African estuary, inferred from acoustic telemetry and long-term seine-netting data - RH Bennett; PD Cowley; A-R Childs; AK Whitfield (African Journal of Marine Science, 2012)

Specific targeting of host individuals by a kleptoparasitic bird - A. R. Ridley; M. F. Child (Behavioral Ecology and Sociobiology, 2009)

Development of the primary bacterial microfouling layer on antifouling and fouling release coatings in temperate and tropical environments in Eastern Australia - Paul J. Molino; Samantha Childs; Maeve R. Eason Hubbard; Janet M. Carey; Mark A. Burgman; Richard Wetherbee (Biofouling, 2009)

Characteristics and economic contribution of a developing recreational fishery in southern Angola - W. M. POTTS; A.‐R. CHILDS; W. H. H. SAUER; A. D. C. DUARTE (Fisheries Management and Ecology, 2009)
The characteristics and contribution of a developing recreational fishery to the local, regional and national economy of Angola were evaluated in 2006. Annual angling effort was 13 435 h, while the estimated total catch of the three target species [leerfish, Lichia amia (L.), west coast dusky kob, Argyrosomus coronus (Griffiths & Heemstra) and shad, Pomatomus saltatrix (L.)], was 5913 fish with a mass of 27 975 kg. Catch per unit effort (CPUE) for all teleost species combined was 0.44 fish per angler h −1 and 2.08 kg per angler h −1 . Total harvest of the three species was 576 fish with a total mass of 2221.6 kg. The total contribution of this recreational fishery (mostly anglers from South Africa) to the local economy was US$ 1007 per harvested fish and US$ 243 per harvested kg. This equated to a contribution to the local, regional and national economies of US$ 151 685, US$ 44 767 and US$ 344 364 respectively. Although the regional contribution was less than half of the national contribution, it was regionally significant when the low population density and the general absence of other formal sector employment opportunities are considered. As a result of the largely undisturbed nature of the southern Angolan coastline, the catch, effort and CPUE information was considered suitable as a baseline for a cost‐effective method of future fisheries monitoring in the region.

Home range of an estuarine‐dependent fish species Pomadasys commersonnii in a South African estuary - A.‐R. CHILDS; A. J. BOOTH; P. D. COWLEY; W. M. POTTS; T. F. NÆSJE; E. B. THORSTAD; F. ØKLAND (Fisheries Management and Ecology, 2008)
The home range and area use of spotted grunter, Pomadasys commersonnii (Haemulidae) (Lacepède), were investigated in the Great Fish estuary, South Africa. Forty individuals (263–698 mm TL) were surgically implanted with acoustic‐coded transmitters and manually tracked during two periods in 2003. Tagged fish spent on average 68 and 77% of the time in the estuary and the remaining time at sea during the two periods, respectively. While in the estuary, there was large variation in home range size, home range length and the number of home range areas amongst individuals. Larger fish had larger home ranges and more core areas than smaller fish. The home ranges of 29 individuals (74%) occurred in the lower reaches of the estuary, suggesting that the proclamation of a no‐take zone in this high use area could benefit this over‐exploited estuarine fishery species.

Molecular mapping of the rf1 gene for pollen fertility restoration in sorghum (Sorghum bicolor L.) - R. R. Klein; P. E. Klein; A. K. Chhabra; J. Dong; S. Pammi; K. L. Childs; J. E. Mullet; W. L. Rooney; K. F. Schertz (Theoretical and Applied Genetics, 2001)

Analysis of lymphoedema-distichiasis families forFOXC2 mutations reveals small insertions and deletions throughout the gene - R. Bell; G. Brice; A. Child; V. Murday; S. Mansour; C. Sandy; J. Collin; A. Brady; D. Callen; K. Burnand; P. Mortimer; S. Jeffery (Human Genetics, 2001)

A suite of highly polymorphic microsatellite markers in turbot ( Scophthalmus maximus L.) with potential for use across several flatfish species - A. Iyengar; S. Piyapattanakorn; D. A. Heipel; D. M. Stone; B. R. Howell; A. R. Child; N. Maclean (Molecular Ecology, 2000)

Indices of skeletal muscle damage and connective tissue breakdown following eccentric muscle contractions - S. J. Brown; R. B. Child; S. H. Day; A. E. Donnelly (European Journal of Applied Physiology, 1997)

Antigenic relationships of murine coronaviruses - J. C. Childs; S. A. Stohlman; L. Kingsford; R. Russell (Archives of Virology, 1983)